Effect of severe plastic deformation on mechanical and fatigue behaviour of medium-c sheet steel - Rusz S.; Hilšer O.; Ochodek V.; Čížek L.; Kraus M.; Mareš V.; Grajcar A.; Švec J. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The DRECE method belongs to the severe plastic deformation (SPD) processes used for the refinement of sheet metal elements. A forming device used in this method is currently being installed in the workplace in the Centre of Advanced Innovation Technologies, VSB Technical University of Ostrava. In the present work the structural characteristics and fracture morphology of Ck55 carbon steel after the application of the DRECE method with a forming tool angle of 118° are presented. The microstructure results are linked to selected mechanical properties. The tensile, hardness, and fatigue tests are performed. The methodology of non-destructive residual stresses measurement in the carbon steel after the extrusion and application of tensile tests on small samples are important for their use in technical practice. The paper presents the original results of selected properties after the application of the DRECE method on Ck55 steel, which will be used in the future to assess the application of the DRECE method and to determine other directions of the processing of ferrous alloys and steels.